Efektivitas Kangkung Air (Ipomoea aquatica) sebagai Fitoremediasi dalam Menurunkan Kadar Timbal (Pb) Air Limbah Batik - Juwita Eka Hapsari; Choirul Amri; Adib Suyanto (Sanitasi: Jurnal Kesehatan Lingkungan, 2018)
Poor controlling mechanism on industrial waste have resulted in very wide pollution, such as li-quid waste containing Pb from batik making industries. Rivers that have been polluted by Pb compounds or ions which exceed the threshold concentration may result in death for aquatic bio-ta. Batik industries in Pilangkenceng has never conducted wastewater treatment. One of the treatment methods that can be applied is by using phytoremediation plants. The purpose of this research was to know the effectiveness of water spinach (Ipomoea aquatica) in decreasing the concentration of lead (Pb) in batik waste water, by conducting a pre-test post-test with control group designed experiment held in December 2017 to February 2018. The study results show that the average of Pb concentration before the treatment was 0,252 mg/l, and by adding five stems of water spinach, the concentration decreased 0,001 mg/l; adding 10 stems of spinach, decreased 0,077 mg/l; and adding 15 stems spinach, decreased 0,112 mg/l. Data analysis with one way anova statistical test at ?=0,05 shows significant difference among those decreases (p-value <0,001.